The Effect of Work Stress, Work Involvement and Organizational Culture on Employee Job Satisfaction at PT JNE Express Main Branch Medan - Ikhsan Mardiansyah; Niken Wulandari; Nashruddin Setiawan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This research was conducted at PT. JNE Ekspres, Medan Main Branch with the aim of analyzing the effect of work stress, work involvement and organizational culture on employee job satisfaction. The population is employees working in the company as many as 55 outbound employees with sampling with saturated samples so that the number of research samples is 55 respondents. The type of data used is primary data and the data source used is secondary data, data collection techniques using literature studies, surveys and observations. Data analysis techniques are multiple linear regression, classical assumption tests and hypothesis tests. The results of the study show that work stress, work involvement and organizational culture partially and simultaneously have a significant effect on employee job satisfaction in the company. There is a strong correlation between work stress, work involvement and organizational culture with employee job satisfaction in the company. The adjusted R2 value = 0.495 means that employee job satisfaction in the company can be explained by work stress, work involvement and organizational culture by 49.5% and the remaining 50.5%% can be explained by other variables not studied such as training, compensation, workload and so on.